2004
DOI: 10.1097/00004728-200401000-00007
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional Computed Tomography Lymphography–Guided Identification of Sentinel Lymph Nodes in Breast Cancer Patients Using Subcutaneous Injection of Nonionic Contrast Medium

Abstract: The present clinical trial indicated that subcutaneous injection of nonionic contrast medium with CT scanning seems to be a promising method for the demonstration of a draining lymph vessel and SLN. The CT value time-course may also provide some important information. Further trials will be needed for the successful establishment of this CT lymphography-guided method for SLN identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…The most commonly used methods for identifying the SLN are the dye-staining method [2, 3] and the radioisotope method [4,5]. We used multidetector-row, three-dimensional computed tomographic (3D-CT) lymphography to mark the precise location of the SLN on the skin before the operation [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used methods for identifying the SLN are the dye-staining method [2, 3] and the radioisotope method [4,5]. We used multidetector-row, three-dimensional computed tomographic (3D-CT) lymphography to mark the precise location of the SLN on the skin before the operation [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used methods for identifying the SLN are the dye-staining method [2, 3] and the radioisotope method [4,5]. We used multidetector-row, three-dimensional computed tomographic (3D-CT) lymphography to mark the precise location of the SLN on the skin before the operation [6][7][8].We have devised a new endoscopic surgical procedure for breast diseases, video-assisted breast surgery (VABS), which has been previously reported [9]. The VABS procedure has three main features: (1) working space is created by the retraction method; (2) almost all surgical procedures are performed through a small axillary or periareolar incisional port; and (3) the breast is reconstructed simultaneously to preserve the preoperative breast shape.…”
mentioning
confidence: 99%
“…LS). Minato et al were also able to predict SNs in 13/15 patients with breast cancer, either by enhancement of the lymphatic vessel draining into the SN, or enhancement in the SN itself, correlating well with blue-dye detection (50). Suga et al have also demonstrated CT detection of SNs in esophageal cancer (51).…”
Section: Computed Tomographymentioning
confidence: 93%
“…We identified the SN using CT-lymphography (CTLG) combined with dye-staining [9,10] because our institution is not equipped with RI facilities. Clinicopathological studies to determine the metastatic status of SNs were performed on 2-mm sections of hematoxylin-eosin (HE)-stained surgical permanent specimens.…”
Section: Methodsmentioning
confidence: 99%